2005
DOI: 10.1213/01.ane.0000154534.71371.4f
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender on Loss of Consciousness with Sevoflurane or Propofol

Abstract: Gender affects the dosing requirements for, and response to, many drugs used in anesthetic practice. Loss of consciousness is an early clinical marker of hypnotic drug effect. We found no significant difference to either an inhaled (sevoflurane) or IV (propofol) anesthetic related to patient gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…Kodaka et al . [10] found that men required significantly more propofol than women at induction (2.9±0.2 v/s 2.7±0.1 mg/kg respectively) but there was no difference in the BIS value at loss of consciousness for men and women. Our study also showed that the decrease in dose of propofol in females compared to males and utilization of propofol for induction in both sexes were less compared to the study of Kodala et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kodaka et al . [10] found that men required significantly more propofol than women at induction (2.9±0.2 v/s 2.7±0.1 mg/kg respectively) but there was no difference in the BIS value at loss of consciousness for men and women. Our study also showed that the decrease in dose of propofol in females compared to males and utilization of propofol for induction in both sexes were less compared to the study of Kodala et al .…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoints used in humans to determine the threshold for LOC during induction of anaesthesia include the patient's inability to respond to non-noxious stimuli such as (i) cessation of counting (Campagna et al 2003); (ii) loss of response to verbal command (Dunnet et al 1994); (iii) suppression of the eyelash reflex (Forrest et al 1994, Gugino et al 2004; (iv) calling out one's name (Glass et al 1997); (v) uninhibited release in a handheld object (Kearse et al 1998);or (vi) light tapping on the shoulder or light shaking (Kodaka et al 2005). In addition, up to 1.3 times the minimum alveolar concentration (MAC) of halogenated volatile anaesthetics supplemented with opioids and nitrous oxide have been recommended for suppression of awareness during anaesthesia in humans (Sandin et al 2000).…”
Section: Definitions Of General Anaesthesiamentioning
confidence: 99%
“…[13] Similar studies conducted with sevoflurane do not suggest any influence of gender on hypnotic requirements. [14] We conclude that use of epidural infusion of local anaesthetic and opioid permits a reduction in the amount of inhalational anaesthetic administered for optimum intraoperative anaesthesia. Immediate recovery and emergence is faster with desflurane when administrated using low flow anaesthesia and titrated to 0.8MAC in patients undergoing long duration cancer surgeries.…”
Section: Discussionmentioning
confidence: 81%
“…Newer volatile anaesthetic agents like desflurane and sevoflurane have significantly lower blood/gas partition coefficient (0.45 and 0.65 respectively) which facilitates rapid emergence from anaesthesia. [1,2] The clinical advantages due to favourable pharmaco kinetic properties of desflurane has been proved beyond doubt after short duration desflurane anesthesia in day care surgeries as well as major surgeries lasting 90-120 minutes, [14][15][16][17][18] but increased duration of anesthesia may amplify pharmacokinetic profile difference between halogenated agents of different solubilities. Epidural bupivacaine and lignocaine reduce the amount of inhalational agent required for maintanence of anesthesia.…”
Section: Introductionmentioning
confidence: 99%